2006
DOI: 10.1016/s1015-9584(09)60295-5
|View full text |Cite
|
Sign up to set email alerts
|

Chylous Ascites After Anterior Resection for Rectal Carcinoma: A Rare But Significant Incident

Abstract: Chylous ascites specifically after anterior resection for rectal cancer has not been documented in the literature thus far. All previously reported postoperative chylous ascites developed in other types of malignancies and were diagnosed within a few days of surgery. However, the patient we report had symptoms 2 years after surgery. Intraoperatively, chylous ascites was found with multiple lymph node metastasis in the small bowel mesentery and retroperitoneal region. The rarity of chylous ascites after anterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Chylous ascites after colorectal surgery is considered to be very rare, and its true incidence remains unclear. Only one study has been reported that describes the incidence of this condition after colorectal surgery in a large population, although there have been several case reports . However, there have been no published data analyzing the etiology, incidence, and treatment of chylous ascites after laparoscopic colorectal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Chylous ascites after colorectal surgery is considered to be very rare, and its true incidence remains unclear. Only one study has been reported that describes the incidence of this condition after colorectal surgery in a large population, although there have been several case reports . However, there have been no published data analyzing the etiology, incidence, and treatment of chylous ascites after laparoscopic colorectal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Our PubMed search for all relevant literature on chylous ascites after colorectal surgery revealed several case reports [8,9,[12][13][14], but extensive information is not available. Hence, the diagnostic criteria, epidemiology, Surg Today (2012) 42:724-728 725 onset features, and treatment of chylous ascites after colorectal cancer remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Expanded lymph node dissection may have caused the higher frequency of chylous ascites in our patient population. We found one published case each of chylous ascites after right hemicolectomy with D3 lymphadenectomy for colorectal cancer, after low anterior resection with D3 lymphadenectomy for colorectal cancer, and after paraaortic lymphadenectomy for recurrent colorectal cancer [8,9,12,13]. A connection between the range of lymph node dissection and the frequency of chylous ascites following colorectal cancer surgery has not been established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In malignant tumours, accumulation of chyle is mainly related to infiltrative growth with consecutive obstruction of lymphatic vessels by tumour cells or external tumour compression. Due to a permanent loss of fluids, proteins, vitamins, fat and T cells, chylous ascites results in malnutrition, dehydration and immune deficiency [31]. Clinically, patients mainly present with a painless distended abdomen, nausea, edema, palpable lymph nodes or with non-specific abdominal pain.…”
Section: Chylous Ascitesmentioning
confidence: 99%